The bonding interactions in fluorinated vinylogous amides: a CF3-substituted carbonyl β-aminoenone as a case study - Espitia Cogollo, Edeimis (2021)
A new perfluoromethylated vinylogous amide, (Z)-4,4,4-trifluoro-1-(2- hydroxyphenyl)-3-(2-methoxyethylamino)-2-buten-1-one, is chosen as an example to investigate the bonding interactions in solid state. The Z, s-cis form is the dominant conformation in both solution and solid state. Intramolecular hydrogen bonding determines this conformational preference in a nonpolar solvent (NMR spectra). Carbonyl and phenol groups are sensitive to the intra- and intermolecular contacts (vibrational spectra). The supramolecular assembly (X-ray diffraction) is governed by NH⋯O and OH⋯O strong intermolecular hydrogen bonds giving rise to center-symmetric R2 2(16) and R2 2(12) graph-set motifs. The -stacking, F⋯H and F⋯F interactions are also discussed (Hirshfeld analysis).